Soil beetles assemblages as ecological indicators in the neotropics: implications for ecosystem conservation and restoration - Cajaíba, Reinaldo Lucas (2018)
Emerging concerns with environmental issues has led researchers to look for indicators capable of providing information on the condition of ecosystems. Several animal species have been used for this role. Among these organisms, ground-beetles were found to be appropriate indicators, since they are adapted to all terrestrial habitats, being associated with ecosystem function and sensitive to ongoing changes. Several families of ground beetles, e. g. Carabidae, Cicindelidae, Scarabaeidae, Cerambycidae, Histeridae, Staphylinidae and Curculionidae were used in diverse ecological assessment studies due to its main characteristics, such as habitat fidelity and taxonomic diversity, and because they provide cheap and easy measurements from functionally diverse trophic chains. Although the growing number of studies on ecological indicators little is known about the ecological patterns in the communities of ground beetles of tropical ecosystems. The present study provides a review on the use of ground beetles as ecological indicators in tropical ecosystems, with focus on the Brazilian Amazon region. We discuss its use for monitoring the effects of anthropogenic induced changes, namely the conversion of forests to agriculture and farming practices, among others on the functioning of tropical systems. We also highlight the major advances and applications employed, as well as proposals for future studies with this group.